Analyzing The Influence of Social Media Marketing, Price Discount, and Product Quality on Purchase Intention: A Study of Mad For Makeup - Rifa Abhista Rizkyah; Corry Yohana; Daru Putri Kusumaningtyas (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The cosmetics industry in Indonesia has experienced rapid growth along with increasing consumer awareness of self-care and the expansion of digital platforms. This study aims to examine the effect of social media marketing, price discount, and product quality on purchase intention toward the Mad For Makeup brand. A quantitative approach was employed using survey data collected from 162 respondents who are beauty enthusiasts in West Java and have been exposed to Mad For Makeup’s social media content. The data were analyzed using multiple linear regression with SPSS 31, including validity, reliability, classical assumption tests, and hypothesis testing. The results indicate that all three independent variables have a positive and significant effect on purchase intention. Among them, product quality is the most dominant factor influencing purchase intention, followed by price discount and social media marketing. These findings suggest that while digital marketing activities and promotional strategies contribute to consumer interest, product quality remains the key determinant in shaping purchase intention in the cosmetics industry. The study provides practical implications for cosmetic brands to strengthen product quality while maintaining effective social media engagement and competitive pricing strategies.